Awareness, benefits, threats, attitudes, and satisfaction with AI tools among Asian and African higher education staff and students (Journal of Applied Learning and Teaching, 2024)
Artificial intelligence (AI) tools are now used in our daily lives. This study aimed to explore the level of awareness, perceived benefits, threats, attitudes, and level of satisfaction with AI tools among individuals within higher education in Asia and Africa. A cross-sectional study was conducted in August 2023. Snowball sampling was used with a convenience sample of 815 highly educated Asian and African participants from 11 countries. About 56% of participants have Bachelor’s degrees. 312 participants (38%) were unaware of AI tools and AI tools were used rarely by 316 (63%) of 503 participants who were aware of them. ChatGPT is the most popular of this study’s AI tools (N=405, 81%). Participants who used AI tools reported greater benefits than those who did not (p < 0.05). ¬Of the four educational groups, those with a Master’s degree reported a higher AI tool threat than those with a Diploma (P < 0.05). Female participants reported more AI-related threats than males (P < 0.05). In conclusion, this research is important because of the rapid development of modern technology around the world. Nevertheless, Asia and Africa still lag behind developed nations in AI technology awareness.